Attention deficits in Brazilian health care workers with chronic pain - Schmidt, Sergio L.; Araguez, Ingrid M.; Neves, Vithória V.; van Duinkerken, Eelco; Schmidt, Guilherme J.; Tolentino, Julio C.; Gjorup, Ana Lúcia T. (Frontiers in Psychology, 2022)
The impact of COVID-19 on chronic pain (CP) in non-infected vulnerable South American subjects is unknown. Healthcare workers (HCWs) are at increased risk for CP. During the pandemic, many HCWs with CP kept working. Knowing how cognition is affected by CP in these subjects is an important subject for work safety. The attention domain has a pivotal role in cognition. Previously, the Continuous Visual Attention Test (CVAT) was applied to detect specific attention deficits in fibromyalgia patients. The present investigation described CP prevalence in non-infected Brazilian HCWs during the pandemic and assessed HCWs’ attentional performance with the aid of the CVAT. This study was carried out at a reference University Hospital in Rio de Janeiro, Brazil. HCWs of both sexes, aged 20 or older, were interviewed from August to December 2020. A 90-second version of the CVAT was performed. The average reaction time to correct responses and the respective intraindividual reaction time variability for correct responses to target (VRT) was determined. Omission and commission errors were also calculated. Then, for each participant we calculated the Z-scores of the CVAT variables based on the distribution of CVAT performance of 211 healthy subjects (reference-comparison group). HCWs with Z-scores > 1.64 were classified as significantly impaired. From the 154 selected HCWs, 72 reported CP during the pandemic (prevalence = 47%). Post hoc ANCOVAs showed that the average correct VRT was significantly higher in the CP group than in the non-CP group (F=4.99, df=1/150, p=0.027, η2=0.032). The percentage of participants with impaired VRT performance was 30% (n=21) in the CP group and 16% (n=13) in the non-CP group. The difference between these two propositions reached significance (χ2 = 3.96, df = 1, p = 0.047). As VRT is associated with the sustained-attention subdomain, our data suggest that this subdomain is disrupted in the CP group.